LEGAL CERTAINTY FOR ETAWAKU GOAT MILK TRADEMARK RIGHTS HOLDERS OVER TRADEMARK CANCELLATION SUIT - Zulaika, Emi; Susanti, Dyah Ochtorina; Hayfa, Jessenia (Awang Long Law Review, 2025)
Information technology encourages globalization and IPR protection, making brands an important asset to differentiate products or services in business competition. This research aims to analyze the first to file principle in the registration of the Etawaku goat milk brand regarding legal certainty and legal consequences. The first to file principle as regulated in Law Number 20 of 2016 concerning Trademarks provides exclusive rights to the first registrant, without regard to previous use. This created a polemic in the case of a dispute between Imam Subekhi, the initial user of the Etawaku brand since 2012, and Mukit Hendrayatno, the official registrant of the brand in 2021 and 2022. This research uses a juridical-normative method with a statutory and conceptual approach. The research results show that the application of the first to file principle has provided legal certainty to the first registrant, namely Mukit Hedrayatno. As a result of the law, Imam Subekhi lost his rights to the brand even though he had used it previously. To protect its rights, early adopters can file a trademark cancellation lawsuit on the grounds of bad faith. Apart from that, it also has consequences for third parties, namely changes in ownership or brand disputes that can confuse consumers regarding the authenticity of the product and affect loyalty, as well as risk canceling contracts or cooperation with business partners if the trademark cancellation lawsuit is granted. This research emphasizes the importance of trademark registration to avoid future disputes and provides recommendations to DJKI to increase socialization and speed up the brand verification process through the latest technology.